Identity conceptions in foreign post-nonclassical sociology - Dobrina O. A. (Innovative technologies in science and education, 2016)
the article presents a review of modern identity concepts in foreign post-nonclassical sociology. Using methods of content analysis and discourse analysis, the author identifies General trends in the development of ideas about identity.
Keywords: социальные отношения; дискурс; идентичность; discourse; social relations; identity; постнеклассическая социология; рефлексивный проект; post-nonclassical sociology; reflexive project